2021
DOI: 10.1136/bcr-2020-237690
|View full text |Cite
|
Sign up to set email alerts
|

New onset adrenal insufficiency in a patient with COVID-19

Abstract: SARS-CoV-2 is the cause of COVID-19. Since the outbreak and rapid spread of COVID-19, it has been apparent that the disease is having multi-organ system involvement. Still its effect in the endocrine system is not fully clear and data on cortisol dynamics in patients with COVID-19 are not yet available. SARS-CoV-2 can knock down the host’s cortisol stress response. Here we present a case of a 51-year-old man vomiting for 10 days after having confirmed COVID-19 infection. He had hypotension and significant hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 10 publications
(20 reference statements)
0
36
0
8
Order By: Relevance
“…For instance, autoptic studies in SARS deceased patients had shown degeneration and necrosis of adrenal cortical cells, and SARS-CoV was identified in the adrenal glands, possibly confirming a direct cytopathic effect [209]. As ACE2 is widely expressed at adrenal levels, it is believed that SARS-CoV-2 may lead to similar detrimental consequences as described for other coronaviruses [209], even if a causal relationship between new-onset PAI and SARS-CoV-2 remains to be confirmed [210,211]. Microscopic examination of the adrenal glands from COVID-19 deceased patients showed acute fibrinoid necrosis of small vessels, mainly arterioles, in adrenal parenchyma, capsule, and periadrenal adipose tissue with subendothelial vacuolization and apoptotic debris without significant signs of inflammation, parenchymal infarctions, or thrombosis [212].…”
Section: Adrenal Glandmentioning
confidence: 85%
“…For instance, autoptic studies in SARS deceased patients had shown degeneration and necrosis of adrenal cortical cells, and SARS-CoV was identified in the adrenal glands, possibly confirming a direct cytopathic effect [209]. As ACE2 is widely expressed at adrenal levels, it is believed that SARS-CoV-2 may lead to similar detrimental consequences as described for other coronaviruses [209], even if a causal relationship between new-onset PAI and SARS-CoV-2 remains to be confirmed [210,211]. Microscopic examination of the adrenal glands from COVID-19 deceased patients showed acute fibrinoid necrosis of small vessels, mainly arterioles, in adrenal parenchyma, capsule, and periadrenal adipose tissue with subendothelial vacuolization and apoptotic debris without significant signs of inflammation, parenchymal infarctions, or thrombosis [212].…”
Section: Adrenal Glandmentioning
confidence: 85%
“…After removing duplicates and implementing inclusion and exclusion criteria, 10 articles (cross-sectional studies: 3, case reports: 7) were enrolled for the current review ( Figure 1 ). AI was defined based on laboratory data, computed tomography (CT) results, or a combination of both methods [ 17 , 18 , 24 , 25 ]. A summary of included studies based on their designs is provided in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of AI was done through CT findings, laboratory profiles, or both in 2 [ 24 , 28 ], 3 [ 17 , 18 , 31 ], and 2 [ 29 , 30 ] patients, respectively. Only one patient died [ 28 ], and all 6 others were discharged in stable condition with appropriate medical treatment [ 17 , 18 , 24 , 29 – 31 ]. 2 patients were followed up after hospital discharge with normal status [ 24 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations